Constraints in Adopting Improved Cauliflower Cultivation Practices in Hardoi, Uttar Pradesh - Verma, Aman; Dr. Adesh Kumar Verma,; R. K. Doharey,; Amrit Warshini,; Gaurav Kumar,; Vineeta Chandra, (Indian Journal of Extension Education, 2025)
The study examined the constraints faced by cauliflower growers in adopting recommended cultivation practices in Hardoi district, Uttar Pradesh, during the Rabi season of 2021–22. Through multistage random sampling method selected 120 farmers across five blocks and ten villages. The results identified significant technical challenges, including "More infestation of insect pests and diseases" (2.60 MS), reported by 79.16% of farmers, and "Lack of disease-resistant varieties" (2.59 MS). Economic barriers such as "High cost of insecticides/pesticides" (2.54 MS) and infrastructural issues like "Lack of storage facilities" (2.52 MS) were also prominent. Credit constraints, led by "Non-availability of credit" (2.18 MS), further compounded farmers’ difficulties. The least significant constraints included "Lack of knowledge about seed treatment" (1.47 MS) and "High cost of irrigation" (1.57 MS). The study concludes that addressing these challenges through enhanced pest management strategies, introducing disease-resistant varieties, and improved economic and infrastructural support could bolster cauliflower cultivation. Such interventions are crucial for improving farmer productivity, ensuring sustainability, and fostering regional agricultural development.